Rembrandt : life of a portrait painter - Spence, David (Hauppage, N.Y. : Barron's, 1997)
Examines the society and art of the world in which Dutch artist Rembrandt van Rijn lived and worked; and provides information about his life, vision, and lasting influence.
Includes index.
Adult
Keywords: Rembrandt Harmenszoon van Rijn, -- 1606-1669.; Rembrandt Harmenszoon van Rijn, -- 1606-1669.; Dutch painters